Islamic Social Ethics Education Model as a Resolution to Moral Degradation through Persuasive Communication - Irhas, Irhas; Kadri, Kadri; Wahid, Abdul (Universitas Muhammadiyah Mataram, 2024)
Abstract:The aim of this research is to identify the patterns of Islamic education conveyed through persuasive communication in the formation of social ethics as a resolution to moral degradation. Data collection for this article was conducted using a qualitative method with library research and a content analysis approach. The results of this study show that the appropriate and effective Islamic education model, delivered through persuasive communication, capable of addressing moral degradation is education that applies the methods of understanding, habituation, and exemplary behavior. Abstrak: Penelitian ini bertujuan untuk mengetahui pola pendidikan Islam yang disampaikan melalui komunikasi persuasif dalam pembentukan etika sosial sebagai resolusi degradasi moral. Pengumpulan data dalam penyusunan artikel ini menggunakan metode kualitatif dengan penelitian kepustakaan dan pendekatan kajian isi. Hasil penelitian ini menunjukkan bahwa model pendidikan Islam yang tepat dan efektif dan disampaikan menggunakan komunikasi persuatif akan mempu menghadapi degradasi moral adalah pendidikan dengan menerapkan metode pemahaman, pembiasaan, dan keteladanan.